Flesh in the Age of Reason - Porter, Roy, 1946-2002; Schama, Simon (New York : W.W. Norton & Company, 2003)
"How did we come to a modern understanding of our bodies and souls? ... Roy Porter charts how, through figures as diverse as Locke, Swift, Johnson, and Gibbon, ideas about medicine, politics, and religion fundamentally changed notions of self"--Page 2 of jacket
Know yourself -- Religion and the soul -- Medicine and the body -- The rational self -- Science rescues the spirit -- John Locke rewrites the soul -- The spectator : the polite self in the polite body -- Shaftesbury and Mandeville -- Swift and the Scriblerans : nightmare selves -- Johnson and incorporated minds -- Edward Gibbon : fame and mortality -- This mortal coil -- Flesh and form -- Putting on a face -- Sexing the self -- Telling yourself -- And who are you? -- Unreason -- Scottish selves -- Psychologizing the self -- Industrial bodies -- Dependent bodies -- William Godwin : awakening the mind -- William Blake : the body mystical -- Byron : sexy satire -- The march of mind
Originally published: London : Allen Lane, 2003
Includes bibliographical references (pages 475-555) and index
Keywords: English literature -- 18th century -- History and criticism; Human body in literature; Enlightenment -- Great Britain; Mind and body in literature; Rationalism in literature; Medicine -- History -- 18th century; Philosophy; Body and soul in literature; History, 18th Century; Human Body; Mind-Body Relations, Metaphysical; Literature, Modern -- history; Philosophy; Sociology, Medical -- history; History, Early Modern 1451-1600; Great Britain -- Intellectual life -- 18th century; United Kingdom